2014
DOI: 10.1007/s10535-014-0410-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR164- and miR167-mediated target gene expressions in responses to water deficit in cassava

Abstract: Cassava (Manihot esculenta Crantz) is an important crop and it is significantly affected by water stress. The computational analysis of cis-regulatory elements in promoter regions of 21 drought-responsive miRNA gene families and 35 miRNA-target genes in cassava indicated some elements relevant to drought stress responses. To investigate the role of miRNAs and target genes in responses to a water deficit in cassava in more detail, in vitro plantlets were subjected to an imitated water deficit by 40 % polyethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Interestingly, we observed that the transcript level of NAC was positively correlated with the accumulation of miR164 in the root of wheat seedlings upon the Cd stress. This result was in agree with that of Phookaew et al (2014), who found that the expression of miR164 and its target MesNAC was not inversely regulated in the roots of cassava during water deficit. Furthermore, the expression of miR156 and its target SBP in both leaf and root tissues of wheat seedlings in our study also showed positive correlation under Cd stress.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we observed that the transcript level of NAC was positively correlated with the accumulation of miR164 in the root of wheat seedlings upon the Cd stress. This result was in agree with that of Phookaew et al (2014), who found that the expression of miR164 and its target MesNAC was not inversely regulated in the roots of cassava during water deficit. Furthermore, the expression of miR156 and its target SBP in both leaf and root tissues of wheat seedlings in our study also showed positive correlation under Cd stress.…”
Section: Discussionsupporting
confidence: 93%
“…The function of miRNA-167 was not very clear in plant stress response until it was recently showed that the transgenic tomato plants overexpressing miRNA-167 exhibited reductions in leaf size and internode length as well as shortened petals, stamens, and styles 49 . In another study, the differential expression of the cassava miRNA-167 target genes (MesARF6/8) were observed to be associated with changes in the leaf shape and stomatal closure towards drought stress 50 .…”
Section: Resultsmentioning
confidence: 96%
“…Several of the conserved miRNAs expressed only in shoot in response to salt, like miR172a and miR393a, targeting genes encoding proteins like AP2/EREBP and auxin receptor in SCF-E3 ligase indicating the involvement of ethylene and auxin in salt tolerance, and more importantly the modulation of hormonal action and signaling in the salt tolerance process. The fact that salt tolerance in plants could be auxin mediated also stems from 1) upregulation of miR171b (S2 File, S3 File), which targets the gene scarecrow-like proteins that negatively regulates GA/auxin action, 2) downregulation of miR167f in shoot in Pokkali (Fig 1) and sma-miR7 in the halophyte S. maritima [21], both targeting ARF, and 3) the reports of accumulation ARF and IAA-Ala under abiotic stress [53,54]. The second line of miRNA mediated salt tolerance in plants could be through influence on transcription factors regulating expression of genes encoding proteins involved in a wide range of biochemical and physiological processes linked to abiotic stress tolerance without the involvement of plant hormones, like NAC, NFYA, TCP, HD-Zip III and Myb, targeted by miR164a/b/f, miR169c, miR319a, miR166 and miR159a, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to others, the members of miR167 has been reported to be drought responsive [52], and Kinoshita et al [53] have reported their downregulation under high osmotic stress, in agreement with the present observation in shoot (S2 File) considering the fact that salt application also creates physiological dryness like situation, at least during the initial phase of treatment. Moreover, the targets of mir167, like ARF and IAA-Ala, have also been reported to accumulate under drought or osmotic stress [53,54]. It is well established that ARF class of transcription factors regulates diverse metabolic and developmental process under abiotic stress for the benefit of the plant [39,55], and downregulation of miR167f in response to NaCl application in the root and shoot tissues of Pokkali, but not in Badami (Fig 1), might be enabling Pokkali to tolerate salinity better than Badami.…”
Section: Plos Onementioning
confidence: 99%